(untitled) (Malaysian Journal of Civil Engineering, 2018)
Most of soil structure interaction methods for analyzing large-section supports such as barrette foundation modeling the barrette and surrounding soil using 3D FE model. In which, the model leads to a large finite element mesh of a large system of linear equations to be solved. In this paper, a Composed Coefficient Technique (CCT) is adapted for analyzing barrette. The technique takes into account the 3D full interactions between barrette and the surrounding soil. Due to the high rigidity of the barrette relative to the surrounding soil, a uniform settlement along the barrette height can be considered. This enables to compose the stiffness coefficients of the soil matrix into composed coefficients, which consequently leads to a significant reduction in the soil stiffness matrix. The validity and the examinations presented in this research work were carried out with an application for analyzing barrette by CCT. This analysis can be extended for modeling the nonlinear behavior of single barrette and barrette-raft. In which, the barrette can be treated as single unit having a uniform settlement.